Students’ Difficulties in Analyzing Experimental Statistics Data - Iyan Irdiyansyah (Pedagogia: Jurnal Ilmiah Pendidikan, 2015)
This paper is aimed to know the students’ difficulties in statistics especially in formulating experimental statistics data. Descriptive method is used to describe and analyze students’ barries in statistics. Students’ work as documentation, questionnaire and interview are used for collecting the data. The data from the documentation, questionnaire, and interview showed that the students have difficulties in the experimental data calculation. There are factors that cause their difficulties in experimental statistics data calculation. First, they seldom read experimental statistic data processing. Second, the experimental formula is more difficult from others statistic formulas. Many tables should be prepared, and taking the conclusion is also becoming students’ difficulties. To overcome these barriers, basic of math or statistics, the usage of suitable teaching method and technique are needed very much. It may change students’ behavior towards this material. Additionally, sharing to friends and students’ perception change will affect their confidence towards experimental statistics data calculation.